LEGAL PROTECTION OF PASPAMPRES WHICH SERVICES ASSIGNED TO SECURE THE PRESIDENT - Danardana Permadi; Mulyono Mulyono; Slamet Riyanto (Jurnal Hukum Jurisdictie, 2023)
This legal research on legal protection for Paspampres soldiers tasked with securing the President aims to examine and formulate forms of legal protection for Paspampres soldiers tasked with securing the President. The formulation of the problem includes: (a) how is the legal protection for Paspampres soldiers in charge of securing the president; and (b) and how to formulate the ideal concept of legal protection for the Paspampres which has the duty to protect/secure the president. The research method used in this research is explanatory with a normative juridical approach. The results of this study indicate that legal protection for soldiers who carry out the task of protecting the President is still low and inadequate with their very heavy duty as a safety, protector, and life shield for the Head of State. Paspampres soldiers are still often blamed when there is a security threat to the President, even though the threat actually comes from the President's lack of/disobedience to the security protocol, while Paspampres soldiers have clearly worked according to the SOP. Protection of Paspampres Soldiers in general with legal protection for other TNI soldiers. Until now, there has been no special protection arrangement for the Presidential Security Forces when it comes to securing the President. The ideal concept for the protection of Paspampres soldiers is to be specifically differentiated and improved in quality, commensurate with the weight of the duties and security of the President. Therefore, it is necessary to make special regulations regarding legal protection for Paspampres Soldiers. One of the contents of the special regulation is that the Paspampres soldiers are not blamed if there is a threat to the President's security due to the President not complying with the security protocol, while the Paspampres soldiers have clearly complied with the SOP in securing the President. The conclusion of this study is the need to formulate special regulations regarding legal protection for Paspampres Soldiers.